A sustainable agriculture indicators in West Nusa Tenggara Province: A multi-dimensional review of economic, social and environmental issues - Prasony, Ilham Akbar Nur; Soedarto, Teguh (Privietlab, 2026)
This study aims to analyze the trends and relationships between the three pillars of sustainable agriculture economic, social and environmental in West Nusa Tenggara (NTB) during the period 2010-2024. This study employed a quantitative approach utilizing secondary data analysis methods. Data were collected from the Central Bureau of Statistics, FAOSTAT and the Ministry of Agriculture, which included variables such as land productivity, Farmer Exchange Rate (NTP), fertilizer use, rural poverty, and greenhouse gas emissions. Data analysis was conducted using descriptive statistical techniques to examine time-series trends and Pearson correlation analysis to identify relationships between variables. The results indicated a decoupling phenomenon between the pillars of sustainability. Economically, rice and corn productivity in NTB shows an increasing trend, but this has a very strong positive correlation with the increase in the use of inorganic fertilizers, which indicates a heavy burden on the environmental pillar (land degradation risk and emissions). On the other hand, the increase in productivity is not followed by a significant increase in the social pillar, where the correlation with farmer welfare (NTP) is relatively weak. This indicates the existence of a food barn paradox: production increases, but high input costs erode farmers' profit margins. This study concludes that the agricultural system in NTB is currently in a High Input, High Risk condition. The proposed policy recommendation is the need for a transition from chemical input-based agriculture (input-driven) to organic efficiency and value-added agriculture (value-driven) to create a balance between economic profitability, social justice and ecosystem sustainability in NTB.